Perilaku agresivitas pada remaja: Bagaimana peranan kondisi keharmonisan keluarga? - Syaharani Zalzabillah Al Zamir; Tatik Meiyuntariningsih; Hetti Sari Ramadhani (INNER: Journal of Psychological Research, 2023)
Abstract This study aims to understand the relationship between family harmony and aggressive behavioral tendencies in adolescents. This method of research is quantified using the data analysis technique of Spearman’s rho. This study was conducted at SMAN 1 Krumbuk with 151 participants aged 15–18 years. The results of this study show that there is a negative relationship between family harmony and adolescent aggressive behavioral tendencies. Therefore, the hypothesis in this study that "There is a negative relationship between family harmony and the tendency of aggressive behavior in adolescents" is acceptable. That is, the higher the level of family harmony, the lower the tendency to behave aggressively in adolescents. Keywords: Trends in Aggressive Behavior; Family Harmony; Teenagers.